Key frame extraction from a big dataset - Agarwal, Mehal (Nanyang Technological University, 2021)
An autonomous vehicle is an automobile platform capable of sensing and reacting to its immediate environment in an attempt to eliminate the need for human drivers. In autonomous driving, taking decisions like overtaking a vehicle or defining a route requires environmental perception, localization, and planning.